PHENOMENOLOGY OF BODY IN THE CONTEXT OF EDUCATION - S. V. VOLKOVA (Высшее образование в России)
The article attempts to analyze the key ideas of the philosophy of Merleau-Ponty in its relationship with the education phenomenon. Borrowed the old idea about education as a cultivation of capacity for logical inference, as well as ability to investigate and to find solutions to problems, the author demonstrates that these notions reflect a false view of reason as somehow separate from motion and body. Basing on the unity of mind and body, the author shows that one of the main goals of education is to engage and disclose body as a source meaning making. The importance of such curriculum areas as drama, dance and music lies in their possibilities for giving students experience of embodiment.